2022
DOI: 10.1093/jacamr/dlac079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic prescribing for ambulatory patients seeking primary dental care services in a public hospital in Ghana: a clinical audit study

Abstract: Background One in 10 of all antibiotic prescriptions globally are for dental conditions with 80% of them being inappropriate, making it a potential driver of antimicrobial resistance. Objectives To evaluate the appropriateness of antibiotic use among ambulatory patients seeking dental care services in a public hospital in Ghana. Methods A retrospective clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Two hospitals in Ghana were the setting for this study: One is a 100-bed hospital in Accra (Ghana’s capital city), and the other is a 110-bed government hospital in a rural area within the Volta Region. These hospitals were selected due to their involvement in a previous AMS project and previous studies of dental antibiotic use [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hospitals in Ghana were the setting for this study: One is a 100-bed hospital in Accra (Ghana’s capital city), and the other is a 110-bed government hospital in a rural area within the Volta Region. These hospitals were selected due to their involvement in a previous AMS project and previous studies of dental antibiotic use [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Whilst dentistry was not included in either of these AMS programmes, recent audits in both hospitals found high rates of dental antibiotic use: dental teams were the highest prescribers of antibiotics, responsible for >20% of antibiotics prescribed in one hospital [ 13 ]. The audits also found high rates of antibiotic misuse: nearly 90% of dental patients in an-other hospital received an antibiotic, of which 88% were non-compliant with national standard treatment guidelines [ 14 ]. This study aimed to explore the antibiotic prescribing behaviour of dental teams and knowledge/beliefs about antibiotic stewardship at these two hospitals in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Sefah, 2022 JAC-antimicrobial resistance [54] Retrospective "Evaluation of antibiotic prescribing for ambulatory patients seeking primary dental care services in a public hospital in Ghana: a clinical audit study"…”
Section: Ono 2020mentioning
confidence: 99%
“…The findings of the various studies about the epidemiology of antibiotic consumption and prescription indicated a lack of adherence to professional guidelines in prescribing antibiotics in dentistry. Only a small percentage of dentists refer to published guidelines for proper antibiotic prescribing, and an even smaller percentage were aware of national action plans on antibiotic resistance [17,18,20,21,28,29,54]. There was still also a lack of knowledge and uniformity in antibiotic prescriptions among dentists in different countries, including Saudi Arabia [18], Pakistan [17], Kuwait [52], Ghana [54], Italy [5], United Kingdom [25], Croatia [30], India [23], Lebanon [39], Northern Ireland [40], and Israel [57].…”
Section: Shemesh 2022mentioning
confidence: 99%
See 1 more Smart Citation